MiR-21 reverses impaired decidualization through modulation of KLF12 and NR4A1 expression in human endometrial stromal cells†. Issue 5 (17th February 2019) - Yan, Qiang; Yan, Guijun; Zhang, Chunxue; Wang, Zhilong; Huang, Chenyang; Wang, Junxia; Zhou, Jidong; Liu, Yang; Ding, Lijun; Zhang, Qun; Zhen, Xin; Jiang, Yue; et al.
Abstract: Impaired decidualization has been considered a major cause of infertility in adenomyosis. However, the mechanism remains poorly understood. Recent studies suggest that microRNAs (miRNA) play a crucial role in embryo implantation. The aim of the present study was to identify the role of miR-21 in human endometrial stromal cell (hESC) decidualization in vitro. To explore the roles of miR-21 in decidualization, we detected the expression of miR-21 in the endometrium of fertile control and adenomyosis patients, and analyzed the effects of miR-21 on the biological behaviors of hESC decidualization. The results demonstrated that miR-21 was downregulated in the endometrium of adenomyosis patients compared with the control endometrium. miR-21 effectively promoted the expression of the 8Br-cAMP plus medroxyprogesterone acetate (MPA)-induced hESC decidualization marker genes PRL and IGFBP-1 and morphological transformation through the modulation of KLF12 and NR4A1 expression; conversely, inhibition of miR-21 expression compromised hESC decidualization in vitro. In addition, Luciferase reporter, western blotting, and quantitative real-time PCR (qRT-PCR) assays confirmed that miR-21 interacted with the 3′ untranslated region of the transcription factor KLF12 and downregulated KLF12 at the transcriptional and translational levels. KLF12 overexpression abolished miR-21-enhanced 8Br-cAMP plus MPA-induced decidualization. Taken together, these results illustrate that miR-21 promotes endometrial decidualization by inhibiting KLF12, and miR-21 overexpression reverses the poor decidual response of hESCs in patients with adenomyosis in vitro. Abstract : miR-21, which is decreased in the endometrium of adenomyosis, reverses impaired decidualization through modulation of KLF12 and NR4A1 expression.